Perspektif Al-Mawardi Konsep Negara dan Kepemimpinan dalam Islam Periode Klasik - Roidatul Fikhriyah (Jurnal Hukum Lex Generalis, 2025)
The concept of state and leadership in Islam according to the perspective of Al-Mawardi, a great thinker in the era of the Abbasid Caliphate. exploring Al-Mawardi's ideas about the function of the state as a tool to achieve the benefit of the people and the role of leadership based on the principles of justice, integrity, Al-Mawardi's thoughts also highlight checks and balances in government to prevent abuse of power. Al-Mawardi's concept of state and leadership remains relevant in building modern governance based on Islamic values. in implementing Al-Mawardi's thoughts on a plural and democratic country. The discussion in the research discusses the formation of the state according to Al-Mawardi's views in the classical period. It can be concluded that ideal leadership is able to maintain political stability and security. Those who had the right to become head of state were required to be from the Quraysh tribe according to the consensus of the ulama. As head of state, he has a fair character, broad insight regarding ijtihad, physical and mental health, and courage in protecting Islamic territory.